2018
DOI: 10.3390/min8030104
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and Geochemical Compositions of the Lopingian Coals in the Zhongliangshan Coalfield, Southwestern China

Abstract: Abstract:The mineralogical and geochemical compositions of the Lopingian coals from an exploratory drill core (ZK4-1) in the Zhongliangshan Coalfield, southwestern China are reported in this paper. The Zhongliangshan coals are medium volatile bituminous in rank (random vitrinite reflectance, average 1.38%), characterized by a medium-ash yield (26.84%) and high sulfur content (3.38%). Minerals in the Zhongliangshan coals are mainly composed of clay assemblages (kaolinite, the illite/smectite mixed layer (I/S) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…In addition to confusing relation between the basaltic Emeishan and the basaltic Kangdian Upland as used by Qin et al, inferring the sediment source region for the coals as the basaltic Emeishan based on Ce and Eu anomalies is incorrect. Dai et al and other subsequent studies , showed that coals with input from the same Emeishan basalts have large positive Eu anomalies. On the basis of the Al 2 O 3 /TiO 2 ratios (12.33–25.44), the low concentrations of V, Sc, Co, Ni, Cu, and Zn, and the distinctively negative Eu anomalies for the K2 coal, Dai et al further concluded that inorganic materials in the K2 coal were dominantly derived from the felsic-intermediate terrigenous rocks at the top of the Emeishan basalt sequence rather than the mafic Emeishan basalts themselves.…”
Section: Geochemistrymentioning
confidence: 82%
“…In addition to confusing relation between the basaltic Emeishan and the basaltic Kangdian Upland as used by Qin et al, inferring the sediment source region for the coals as the basaltic Emeishan based on Ce and Eu anomalies is incorrect. Dai et al and other subsequent studies , showed that coals with input from the same Emeishan basalts have large positive Eu anomalies. On the basis of the Al 2 O 3 /TiO 2 ratios (12.33–25.44), the low concentrations of V, Sc, Co, Ni, Cu, and Zn, and the distinctively negative Eu anomalies for the K2 coal, Dai et al further concluded that inorganic materials in the K2 coal were dominantly derived from the felsic-intermediate terrigenous rocks at the top of the Emeishan basalt sequence rather than the mafic Emeishan basalts themselves.…”
Section: Geochemistrymentioning
confidence: 82%
“… 8 , 11 , 88 92 The late Permian coals in southwestern China have been reported repeatedly for enrichment of REY. 9 , 23 , 27 , 42 , 68 , 93 Seredin and Dai proposed the cut-off grade of oxides of REY in coal ash (1000 μg/g) and an evaluation index, outlook coefficient (C outl ). 11 REY with the C outl > 2.4, 0.7 ≤ C outl < 1.9, and C outl < 0.7 represent highly promising, promising, and unpromising, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium is a critical metal in China, United States, the EU, and many other countries. Many attempts have been made to recover Li from coal ash. , Though there is a relatively high Li concentration in Chinese coals, it is still much lower than the Chinese industrial indicator for recovery of associated Li 2 O (0.2%) . Only coals from a few coalfields, such as Jungar and Pingshuo coals, have reached the industrial indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium is one of the most highly investigated critical metals in Chinese coals. The Late Carboniferous–Early Permian coals in the north of North China Craton are the most well-known Li-rich coals. The concentration of Li in No. 6 coal of the Heidaigou Mine, Jungar Coalfield, Inner Mongolia is 657 μg/g, and the concentration in No.…”
Section: Introductionmentioning
confidence: 99%